IDENTIFIKASI PENGARUH PARAMETER ELEMEN PEMBAYANG TERHADAP PAPARAN RADIASI PADA HUNIAN VERTIKAL - Khalid, Fikri Azmi Nur; Larasati, Dewi; Indraprastha, Aswin (Jurnal Arsitektur ARCADE, 2023)
Abstract: Environmental problems are caused by climatic conditions and the results of sunlight entering buildings that cannot be controlled. Shading device become part of the building and interact directly with the environment and space in the building. Shading device can be applied to buildings to respond to environmental conditions such as solar radiation. Conditioning solar radiation entering buildings can be reduced to reduce building energy use. The results of this simulation show that the length (P) and angle (S) parameters have a significant positive effect on decreasing the intensity of solar radiation. Elements of the Horizontal Louvers type with a change in the value of the Angle (S) parameter from the basic design results in a decrease in radiation intensity of up to 44.3% when the angle changes to 150 with respect to the horizontal wall. In the Brise-Soleil Semi FaÃ§ade With Louvers type, changing the value of the Length parameter (P) from the basic design results in a decrease in radiation intensity of up to 40.3% in the shading element with a length of 0.8 meters. On the other hand, changes in the distance parameter (J) of the shading element to the horizontal wall tend to increase the intensity of solar radiation. In the Horizontal Louvers type, the change in the parameter Distance (J) to the wall with a distance of 0.3 meters from the horizontal wall results in an increase in intensity of up to 81.1% when compared to the design basis.Keyword: Shading Device, Solar Radiation, Design Parameters, Vertical HousingAbstrak: Permasalahan lingkungan disebabkan oleh kondisi iklim dan akibat sinar matahari yang masuk ke bangunan yang tidak dapat dikendalikan. Perangkat peneduh menjadi bagian dari bangunan dan berinteraksi langsung dengan lingkungan dan ruang di dalam bangunan. Shading device dapat diterapkan pada bangunan untuk merespon kondisi lingkungan seperti radiasi matahari. Pengkondisian radiasi matahari yang masuk ke gedung dapat dikurangi untuk mengurangi penggunaan energi gedung. Hasil simulasi menunjukkan bahwa parameter panjang (P) dan sudut (S) berpengaruh positif signifikan terhadap penurunan intensitas penyinaran matahari. Elemen tipe Horizontal Louvers dengan perubahan nilai parameter Angle (S) dari desain dasar menghasilkan penurunan intensitas radiasi hingga 44,3% ketika sudut berubah menjadi 150 terhadap dinding horizontal. Pada tipe Brise-Soleil Semi FaÃ§ade With Louvers, perubahan nilai parameter Length (P) dari basic design menghasilkan penurunan intensitas radiasi hingga 40,3% pada shading element dengan panjang 0,8 meter. Sebaliknya, perubahan parameter jarak (J) elemen peneduh ke dinding horizontal cenderung meningkatkan intensitas penyinaran matahari. Pada tipe Horizontal Louvers, perubahan parameter Jarak (J) ke dinding dengan jarak 0,3 meter dari dinding horizontal menghasilkan peningkatan intensitas hingga 81,1% jika dibandingkan dengan desain dasar.Kata Kunci: Elemen Pembayang, Radiasi Matahari, Parameter Desain, Hunian Vertikal